Pesquisa em Resolução de Problemas: caminhos, avanços e novas perspectivas - Onuchic, Lourdes De La Rosa [UNESP]; Allevato, Norma Suely Gomes [UNESP] (My University, 2011)
We discuss the knowledge that has been constructed regarding Problem Solving in Math Education as a result of research developed by GTERP - Work and Study Group in Problem Solving, UNESP-Rio Claro/SP. The research is guided by the following general questions: How do students construct mathematical knowledge and how do teachers implement the methodology of Math Teaching-Learning-Evaluation through Problem Solving? Historical aspects of Problem Solving are very important in the configuration of the current trends for Problem Solving. One of them is the Methodology of Math Teaching-Learning- Evaluation through Problem Solving, based on clear foundations and an approach of renewal. In addition to that methodology, two aspects have been developed by the group: The conception of Math as a science of pattern and order and Discrete Mathematics. The knowledge constructed and the scientific production of GTERP prove its relevant contribution to intensifying dialogues between research and educational practice, students and teachers, and to increasing the possibilities of that practice particularly in Math work.
Research on problem solving: Directions, advances and new perspectives
Keywords: Math teaching-learning-evaluation; Problem solving; Research in math education; Research on problem solving